Influence of Care Pathway on Thyroid Nodule Surgery Relevance: A Historical Cohort Study - Castellnou, Solène (J Clin Med, 2020)
Background: Guidelines recommend using fine-needle aspiration cytology (FNAC) to guide thyroid nodule surgical indication. However, the extent to which these guidelines are followed remains unclear. This study aimed to analyze the quality of the preoperative care pathway and to evaluate whether compliance with the recommended care pathway influenced the relevance of surgical indications. Methods: Nationwide historical cohort study based on data from a sample (1/97th) of French health insurance beneficiaries. Evaluation of the care pathway of adult patients operated on between 2012 and 2015 during the year preceding thyroid nodule surgery. The pathway containing only FNAC was called “FNAC”, the pathway including an endocrinology consultation (ENDO) with FNAC was called “FNAC+ENDO”, whereas the no FNAC pathway was called “NO FNAC”. The main outcome was the malignant nature of the nodule. Results: Among the 1080 patients included in the study, “FNAC+ENDO” was found in 197 (18.2%), “FNAC” in 207 (19.2%), and “NO FNAC” in 676 (62.6%) patients. Cancer diagnosis was recorded in 72 (36.5%) “FNAC+ENDO” patients and 66 (31.9%) “FNAC” patients, against 119 (17.6%) “NO FNAC” patients. As compared to “NO FNAC”, the “FNAC+ENDO” care pathway was associated with thyroid cancer diagnosis (OR 2.67, 1.88–3.81), as was “FNAC” (OR 2.09, 1.46–2.98). Surgeries performed in university hospitals were also associated with thyroid cancer diagnosis (OR 1.61, 1.19–2.17). Increasing the year for surgery was associated with optimal care pathway (2015 vs. 2012, OR 1.52, 1.06–2.18). Conclusions: The recommended care pathway was associated with more relevant surgical indications. While clinical guidelines were insufficiently followed, compliance improved over the years.